If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12-5*6-5*3=0
We simplify the equation to the form, which is simple to understand
12-5*6-5*3=0
Simplifying:
12-30-5*3=0
Simplifying:
12-30-15=0
We move all terms containing to the left and all other terms to the right.
0=0-12+30+15
We simplify left and right side of the equation.
0=+33
0=33
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 15x-8=4+9x | | 3m-5m-12-7m-88=50 | | 3x(4+6)=87 | | x^2-3x+6=0 | | 2(x-1)+7x=-20 | | 7(6-x)=16+(2-4x) | | -z^2-4z=-2 | | 6(x-6)+6=8(x+2)-6 | | 3x^2-60x+192=0 | | 5x^2+3x=1 | | h^2-2h-2=0 | | (8x+2)*(7-6x)= | | -3p^2+17p=20 | | 45-x=170 | | -7d^2+9=0 | | 2n^2-6n=8 | | -7x=182 | | 9x-12=42 | | -105+35x=0 | | 2w^2-28w=-98 | | 4x^2+17x-196=0 | | 2(3x-2)=7x | | 4x^2+17x=0 | | x-8=-6+3 | | 11(x-4)=-2-9 | | 6x+18-5x=-3-13 | | -5-4=-6+x | | 4(x-5)=27 | | (8x+2)-(7-6x)= | | 24x+8-27x=2-6 | | -x+(-4+7-3)-(-2-x+4-3)= | | 3(2x+5)=4x+7-x+1 |